External Factors Influencing Consumer Purchase Interest For Herbal Tea Products In Indonesia - Saira, Sifa; Maulana Agung; Gita Paramita Djausal (International Journal of Economics, Business and Innovation Research, 2026)
As more people in Indonesia become concerned about their health, body image, and natural eating habits, herbal weight loss teas are gaining popularity. This creates a competitive market, making it crucial to understand the drivers of consumer purchasing interest. The purpose of this study is to determine the external factors specifically, social and technological factors that affect Indonesian consumers' interest in buying weight loss tea. based on the understanding that purchasing interest is a stage in the purchasing decision process, where consumers form preferences for a product and intend to purchase in the future. Previous research has focused more on internal attributes so there is still a gap in seeing how external factors influence consumer purchasing interest. Using a quantitative methodology and an explanatory research design, this study collected data from 100 respondents who were worried about their weight. The degree to which many independent factors partially and simultaneously affect the dependent variable was ascertained using multiple linear regression analysis. The findings demonstrated that purchasing interest is positively and significantly impacted by sociocultural and technological aspects. According to the regression model, these two independent variables account for 24.2% of the variation in consumer purchasing interest. The results reflect that influencing purchasing interest, Consumers not only consider the benefits of the product but also match their choices with social trends, and cultural values, as well as the encouragement of technological progress.